Total Flavonoids in Premna Fulva Craib Alleviates Brain Neurological Impairment and Influences Nrf2 and HO-1 Expressions in Rats with Ischemia-Reperfusion: Influences Nrf2 and HO-1 Expressions in Ischemia-Reperfusion - Qin, Hui; Fu, Youxue; Jiang, Ying; Tian, Zhao; Zhang, Yongquan; Tan, Wenlan; Liang, Mingkun; Wen, Haicheng; Fang, Gang (Cellular and Molecular Biology, 2022)
Total flavonoids in Premna fulva Craib (TFPFC) are a kind of flavonoid compound synthesized via photosynthesis extracted from Premna fulva Craib, which possess a strong anti-oxidative effect. Cerebral Ischemia-Reperfusion refers to the body's damage mainly caused by oxidative stress. This study aims to investigate the alleviating effect of TFPFC on brain neurological impairment and its influences on Nuclear factor E2-related factor 2 (Nrf2) and heme oxygenase 1 (HO-1) expressions in rats with Ischemia-Reperfusion. The rat model of Ischemia-Reperfusion was established, and rats were treated with TFPFC or normal saline. At 24 h after reperfusion, the neurological score, volume of cerebral infarction and cerebral water content were analyzed in different groups. The influences of TFPFC treatment on the proliferative activity and apoptosis of oxygen and glucose deprivation/reoxygenation (OGD/R) neural stem cells were detected via methyl thiazolyl tetrazolium (MTT) assay and flow cytometry. Moreover, the malondialdehyde (MDA) level and superoxide dismutase (SOD) activity were measured to evaluate the oxidative stress effect. The influences of TFPFC treatment on the protein and messenger ribonucleic acid (mRNA) expressions of Nrf2 and HO-1 were analyzed using reverse transcription-polymerase chain reaction (RT-PCR) and Western blotting. The TFPFC treatment alleviated the neurological impairment in rats after Ischemia-Reperfusion and reduced the volume of cerebral infarction and cerebral edema status in rats with Ischemia-Reperfusion. TFPFC increased the proliferative activity of OGD/R neural stem cells and decreased damage and apoptosis. In addition, the TFPFC treatment reduced the MDA level, improved the SOD activity, and up-regulated the protein and mRNA expressions of Nrf2 and HO-1. The TFPFC treatment may improve oxidative damage and protect the nervous system through the up-regulation of expressions of transcription factors Nrf2 and HO-1.